Implementasi Kecerdasan Visual Spasial Pada Pembelajaran Fisika Melalui Metode Penugasan Pada Materi Gerak - Rondonuwu, Anneke T; Tumangkeng, Jeane; Tingginehe, Ricky Yeftris (Universitas Negeri Manado, 2020)
The objective of this study is to improve students' thinking abilities witu spatial visual intelligence through the assignment method of mation material (GLB, GLBB, and Parabolic Motion). The results of this study indicate that in cycle 1 resulted in students' learning completeness with the criteria for learning completeness in a straight motion of 1235 or achieving an average score of 61.8. Secondly, in straight motion change irregularly 1215 with an average value of 61.5, and the second cycle of the evaluation results obtained an increase in student learning outcomes with an average achievement of 75 and above with achievements that score, meaning that in this second cycle the average value obtained by students in GLB is 82.5, GLBB is 79.5 and in Parabolic Motion is 78.5 and all students complete with 100% completeness. Based on student learning outcomes researchers provide some input to the teacher how to improve students' visul spatial abilities on motion material (GLB, GLBB, and Parabolic Motion). Researcher hopes this skripsi will be useful for education in North Sulawesi.Keywords: Spatial visual intelligence, assignment methods for motion material, (GLB, GLBB, and Parabolic Motion)